If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = 7v + -1v Combine like terms: 7v + -1v = 6v 36 = 6v Solving 36 = 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 36 + -6v = 6v + -6v Combine like terms: 6v + -6v = 0 36 + -6v = 0 Add '-36' to each side of the equation. 36 + -36 + -6v = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -6v = 0 + -36 -6v = 0 + -36 Combine like terms: 0 + -36 = -36 -6v = -36 Divide each side by '-6'. v = 6 Simplifying v = 6
| 20=16-1/4b | | 15c^2-28c+5= | | F(x)=3(1-2x) | | -2(4+6x)=-4-8x | | 3c+9=8c-4-13c | | 18+8k=2(7k+8)-6k | | x+(x+7.2)=13.0 | | 2y-3=5y+9 | | 3/6.35 | | 1+2b-13=4b-2b | | 1-2t=3t+11 | | 14.70x-x=0 | | q^2+10q-16=0 | | -w+134=269 | | 2g-1=1-2g | | 8=-v+244 | | 5c=6+2c | | 202-y=103 | | 7(4c+5)=9-4c+16 | | 164=-x+54 | | -30=6v | | 5v+1=v-7 | | 21-x=241 | | 2091=5+4 | | -3x-4(6y-6x)+5y= | | -24=2u | | 194-x=108 | | 4+5t=3t+10 | | cos74=w/5 | | 63=-v+265 | | 3x+4(-1-2x)=7-8x | | 5+2f=8+1f |